The history of Nguyễn Vietnam-Singapore trade, 1820-1847 - Cao, Thi Van (Nanyang Technological University, 2021)
This thesis breaks away from the Sino-centric ideas in terms of politics and commerce to see Vietnam as a dynamic partner of Singapore’s trade. While the outbreak of the First Opium War created, to some extent, ruptures in the mid-nineteenth century Sino-Vietnamese trade, the opening of Singapore in 1819 attracted merchants from Vietnam, and a considerable number of Vietnam-based junks and boats of large and small sizes visited to this settlement for business. Nguyễn Vietnam’s overseas trade with the Nanyang in the precolonial period, nevertheless, has received little attention from scholars, which leaves a feeling that Vietnam’s commerce with the other Southeast Asian countries was insignificant. This study aims to provide a broader picture of a dynamic Vietnamese trade in intra-Asia commercial networks through a quantitative and qualitative analysis. This thesis attempts to explore the possibility that there was a new era of Vietnam’s commercial history: while eighteenth-and early-nineteenth-century Vietnam relied on Chinese junks for its trade with other parts of Southeast Asia, the second quarter of the nineteenth century saw a rise in Vietnamese owned shipping in the Nanyang. Vietnamese players came to play a more active role in the maritime trade. The Vietnam-Southeast Asia trade came to be dominated by three groups: the Vietnamese King’s ships, the Vietnamese-owned topes , and the junks owned by Chinese settlers in Vietnam. However, the gap in the history of these commercial relations in the late 1830s and 1840s poses a question that this thesis seeks to answer: who was driving the Nguyễn Vietnam-Singapore trade in the context of the Vietnamese government’s trading restrictions. A quantitative method will be adopted in this thesis to see how the Vietnamese government, the local Vietnamese, and the Chinese settlers contributed to the Vietnam-Singapore trade from1820 to 1847. Following the rise of local Vietnamese tope trade in the Malay Peninsula, the study investigates the commercial participation of the natives and the Chinese settlers, showing how the latter gradually escaped the royal prohibitions and sought their trading opportunities through the operation of the Nguyễn’s Tào vận.